Solve for C_1
C_{1}=-\frac{1-h}{2L\left(r+1\right)}
r\neq -1\text{ and }L\neq 0\text{ and }h\neq 1
Solve for L
L=-\frac{1-h}{2C_{1}\left(r+1\right)}
r\neq -1\text{ and }C_{1}\neq 0\text{ and }h\neq 1
Share
Copied to clipboard
LC_{1}\times 2\left(r+1\right)=h-1
Multiply both sides of the equation by 2\left(h-1\right), the least common multiple of h-1,2.
2LC_{1}r+LC_{1}\times 2=h-1
Use the distributive property to multiply LC_{1}\times 2 by r+1.
\left(2Lr+L\times 2\right)C_{1}=h-1
Combine all terms containing C_{1}.
\left(2Lr+2L\right)C_{1}=h-1
The equation is in standard form.
\frac{\left(2Lr+2L\right)C_{1}}{2Lr+2L}=\frac{h-1}{2Lr+2L}
Divide both sides by 2Lr+2L.
C_{1}=\frac{h-1}{2Lr+2L}
Dividing by 2Lr+2L undoes the multiplication by 2Lr+2L.
C_{1}=\frac{h-1}{2L\left(r+1\right)}
Divide h-1 by 2Lr+2L.
LC_{1}\times 2\left(r+1\right)=h-1
Multiply both sides of the equation by 2\left(h-1\right), the least common multiple of h-1,2.
2LC_{1}r+LC_{1}\times 2=h-1
Use the distributive property to multiply LC_{1}\times 2 by r+1.
\left(2C_{1}r+C_{1}\times 2\right)L=h-1
Combine all terms containing L.
\left(2C_{1}r+2C_{1}\right)L=h-1
The equation is in standard form.
\frac{\left(2C_{1}r+2C_{1}\right)L}{2C_{1}r+2C_{1}}=\frac{h-1}{2C_{1}r+2C_{1}}
Divide both sides by 2C_{1}+2C_{1}r.
L=\frac{h-1}{2C_{1}r+2C_{1}}
Dividing by 2C_{1}+2C_{1}r undoes the multiplication by 2C_{1}+2C_{1}r.
L=\frac{h-1}{2C_{1}\left(r+1\right)}
Divide h-1 by 2C_{1}+2C_{1}r.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}